Acronyms, an effective resource in the peruvian press - Gonzales Cruz, Eliana (2018)
Nowadays the use of acronyms is of great interest and importance due to the predominance they have in written documents (newspapers, magazines, books, reports, etc.); however, we can also see their use in the mass audiovisual media such as radio and television, in both aspects they are used to identify the names of institutions of all kinds. This use is well reflected in the ability to synthesize and save space in terms of letters and words. In that sense, this study, through a descriptive analysis, is oriented to explain what conditions the use of acronyms as an effective resource, because when they are used or mentioned in headlines they can be unintelligible to the reader or listener due to the lack of awareness of their meaning or of the formal rules applied to their construction, distinguishing their typology. Finally, it is important to highlight that their use is more recurrent in the journalistic field, where there are limited spaces available and you are obliged to comply with them.